The Quality of Yogurt Drink with Guar Gum and Cornstarch as Stabilizer - Premy Puspitawati Rahayu; Desi Unur; Fathimah Fathimah; Elsa Nursafitri; Bintang Asadel; Citra Nur Yunita; Purwadi Purwadi; Imam Tohari; Firman Jaya (Livestock and Animal Research, 2025)
Objective: This study aims to determine the effect of using guar gum and cornstarch as stabilizers in Yoghurt drinks and to determine the stability of Yoghurt drinks.Methods: The method used 2 stages of research. Stage 1 of the research used a completely randomized design (CRD) with 6 treatments and 3 replicates, T0 (Control); T1 (0.4% Guar gum); T2 (0.3% Guar gum and 0.1% cornstarch), T3 (0.2% Guar gum and 0.2% cornstarch), T4 (0.1% Guar gum and 0.3% cornstarch), and T5 (0.4% Cornstarch). Stage 2 of the study used a completely randomized design (CRD) nested pattern related to different storage periods, H1 (7 days), H2 (14 days), H3 (21 days), H4 (28 days), H5 (35 days) with the same treatment and replication. Data were analyzed using the Analysis of Variance.Results: The results of stage 1 showed that guar gum and cornstarch as stabilizers had a significant effect (P<0.01) on viscosity, syneresis, and water holding capacity, significant effect (P<0.05) on pH, protein, lactose, and showed that no significant effect (P>0.05) on fat, moisture, total titratable acidity, and LAB content. The results of stage 2 showed that different storage periods had a very significant effect (P<0.01) on viscosity and pH. There was no significant effect (P>0.01) on LAB content.Conclusions: It was concluded that guar gum and cornstarch can maintain the quality of the Yoghurt drink for 6 weeks of storage.